Building a Quality Framework for Education: Semantic Study in QS. Al Ma'un and Its Implementation in Learning in Primary School - Yusmaliana, Desfa; Suryadin, Asyraf; Perawironegoro, Djamaluddin; Hendrik, Maulina (J-MPI (Jurnal Manajemen Pendidikan Islam), 2020)
The purpose of this study was to analyze the educational quality framework based on the sematic study in QS. Al Ma'un's and its implementation in learning in the fourth grade of SD STKIP Muhammadiyah Bangka Belitung. This research used descriptive qualitative research methods. The primary data sources of this research were Al Ma'un Surah Al-Qur'an, headmaster, teachers and 4th-grade students of SD STKIP Muhammadiyah Bangka Belitung, while secondary data sources were in the form of relevant research results and documentation. Data collection techniques used content analysis techniques, interviews, questionnaires, and documentation. Data analysis techniques were reducing data, displaying data, making conclusions and verification. The results obtained in this study: 1) QS. Al Ma'un with 7 verses contains the true meaning of religious deceiver and deceit the day of retribution. Their main characters are arbitrary to orphans and do not want to help the poor. Threating to hypocrites who neglect their prayers, showing up their prayers to people even though often leave the prayers and negligent their goals. They also do not want to help others, even lending something to people, even less to give charity and pay zakat. These are the wretched people. 2) the implementation of QS. Ma'un in 4th grade learning at SD STKIP Muhammadiyah Bangka Belitung is praying to worship on time and in a group, giving charity, and having social community programs.